2021
DOI: 10.1021/acsami.1c04659
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Transferred GaN-Based Light-Emitting Diodes through Oxygen-Assisted Plasma Patterning of Graphene

Abstract: Two-dimensional (2D) release layers are commonly used to realize flexible nitride films. Here, high-quality, large-area, and transferable nitride films can be precisely controlled grown on O2-plasma-assisted patterned graphene. The first-principles calculation indicates that the patterned graphene introduced by O2 plasma changes the original wettability of sapphire and the growth behavior of Al atoms is related with layer number of graphene, which is consistent with experimental results. The as-fabricated viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Though vdWE has advantages for the device fabrication, the dislocation density in GaN grown by this method is still as high as 10 9 cm –2 . For some devices, such as laser diodes, a lower dislocation density is often required. Kim et al reported a technique called remote epitaxy by which a single-crystalline GaN film was achieved on graphene interlayer through a remote atomic interaction between substrates and the epi-layer .…”
Section: Introductionmentioning
confidence: 99%
“…Though vdWE has advantages for the device fabrication, the dislocation density in GaN grown by this method is still as high as 10 9 cm –2 . For some devices, such as laser diodes, a lower dislocation density is often required. Kim et al reported a technique called remote epitaxy by which a single-crystalline GaN film was achieved on graphene interlayer through a remote atomic interaction between substrates and the epi-layer .…”
Section: Introductionmentioning
confidence: 99%
“…proposed a new growth method using the O 2 ‐plasma‐assisted patterned graphene and AlN buffer layer to achieve high‐quality and transferable GaN films, and eventually they succeeded in fabricating high‐performance violet LEDs. [ 38 ] By comparing the growth situation of Al atoms on graphene and sapphire, they found that Al atoms had higher migration distance, lower adsorption energy, and lower nucleation density in the graphene region. Additionally, they investigated the effect of the number of graphene layers on the growth behavior of the AlN buffer layer.…”
Section: Epitaxial Layer Lift‐off Techniques Based On 2d Materialsmentioning
confidence: 99%
“…(a3) Reproduced with permission. [ 38 ] Copyright 2021, American Chemical Society.) b) chemical release by etching of a sacrificial layer; ((b1) Reproduced with permission.…”
Section: Introductionmentioning
confidence: 99%
“…Ning et al [8] obtained a stress-free GaN film with optimal quality and a low density of dislocations on Al 2 O 3 by incorporating a sputtered AlN/Gr composite layer in 2020. Jia et al [9] found that high-quality, large-area and transferable nitride films can be accurately controlled and grown on O 2 plasma-assisted patterned Gr substrates.…”
Section: Introductionmentioning
confidence: 99%